2021
DOI: 10.1073/pnas.2024500118
|View full text |Cite
|
Sign up to set email alerts
|

Distinct contribution of cone photoreceptor subtypes to the mammalian biological clock

Abstract: Ambient light detection is important for the synchronization of the circadian clock to the external solar cycle. Light signals are sent to the suprachiasmatic nuclei (SCN), the site of the major circadian pacemaker. It has been assumed that cone photoreceptors contribute minimally to synchronization. Here, however, we find that cone photoreceptors are sufficient for mediating entrainment and transmitting photic information to the SCN, as evaluated in mice that have only cones as functional photoreceptors. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…In addition, studies have also shown that UV light detected by UV-sensitive cone photoreceptors (S-cones) will induce electrical responses in the SCN, along with phase-shifts in circadian activity rhythms [ 23 , 24 ]. Significantly, this input is sufficient for entrainment in the absence of melanopsin and rod photoreceptor signalling [ 25 ]. Finally, photoentrainment will occur following stimulation of the green-light sensitive M-cones.…”
Section: Photoreception For Entrainmentmentioning
confidence: 99%
“…In addition, studies have also shown that UV light detected by UV-sensitive cone photoreceptors (S-cones) will induce electrical responses in the SCN, along with phase-shifts in circadian activity rhythms [ 23 , 24 ]. Significantly, this input is sufficient for entrainment in the absence of melanopsin and rod photoreceptor signalling [ 25 ]. Finally, photoentrainment will occur following stimulation of the green-light sensitive M-cones.…”
Section: Photoreception For Entrainmentmentioning
confidence: 99%
“…[5][6][7] The three cone cell subtypes in the human retina respond maximally to 420-nm, 534-nm, and 563-nm light, while rod cells respond maximally to 498-nm light. 8 In rodents, input from cone cells renders the SCN sensitive to a broad spectrum of wavelengths, 9 while rod cells mediate the SCN's sensitivity to low-intensity light. 10,11 Recently, these findings in rodents were proposed to translate to humans, 12 suggesting that the human clock is not only sensitive to blue light, but may also be sensitive to other colors.…”
Section: Introductionmentioning
confidence: 99%
“…The ipRGCs project via the retinohypothalamic tract (RHT) to the suprachiasmatic nucleus (SCN) of the hypothalamus, the location of the circadian clock in mammals, enabling photoentrainment of the SCN circadian pacemaker ( Moore and Lenn, 1972 ). Following activation by light, glutamate is released at the nerve terminal ( Johnson et al, 1988 ; Ding et al, 1994 ), which leads to an increase in SCN neuronal activity ( Meijer et al, 1992 , 1998 ; Cui and Dyball, 1996 ; Aggelopoulos and Meissl, 2000 ; Nakamura et al, 2004 ; Drouyer et al, 2007 ; Van Oosterhout et al, 2012 ; Van Diepen et al, 2013 , 2014 , 2021 ). The increase in electrical activity in the SCN in response to light consists of a transient onset response and a subsequent sustained response, where activity remains increased for the total duration of the light pulse ( Meijer et al, 1998 ).…”
mentioning
confidence: 99%
“…These mice lack functional rod signalling, due to a targeted deletion of the rod transducing alpha subunit Gnat1 , and melanopsin in the ipRGCs, due to the Opn4 knockout ( Mrosovsky and Hattar, 2005 ). As a consequence, the mutant mice show a reduction in phase shifting capacity and the sustained electrophysiological response in the SCN to the visible light wavelengths ( Van Diepen et al, 2021 ).…”
mentioning
confidence: 99%